A bandit's tale : the muddled misadventures of a pickpocket - Hopkinson, Deborah (Alfred A. Knopf, 2016)
In March of 1887, Rocco, an eleven-year-old from an Italian village, arrives in New York CIty where he is forced to live in squalor and beg for money as a street musician, but he finds the city's cruelty to children and animals intolerable and sets out to make things better, whatever the cost to himself.